Previously undocumented diversity and abundance of cryptic species: a phylogenetic analysis of Indo-Pacific Arminidae Rafinesque, 1814 (Mollusca: Nudibranchia) with descriptions of 20 new species of Dermatobranchus - Gosliner, Terrence M (Blackwell Publishing Ltd, 2011)
The phylogenetic relationships amongst the Arminidae were analysed based upon morphological characters of 58 presently described species or nudibranchs, including 35 previously described Arminidae and 20 new species of Dermatobranchus. From the literature review and anatomical examinations, 43 characters were considered for 78 taxa. These characters were polarized using Berthella canariensis as the outgroup taxon and the type species of several other genera identified from recent publications. The resulting phylogeny supports the monophyly of Arminidae, Dermatobranchus, Doridina, and Proctonotidae. The paraphyly of the Arminina is further demonstrated in this study. Two previously described, but poorly known, species of Indo-Pacific Armina are redescribed, Armina magna Baba, 1955 and Armina paucifoliata Baba, 1955. The anatomy and taxonomic status of nine previously described species of Dermatobranchus were examined in this study. The anatomy of Dermatobranchus pustulosus (van Hasselt, 1824) has been overlooked since Bergh (1888) illustrated the radula of van Hasselt's specimen. It is redescribed and its range is extended to several new localities in the western Pacific. Dermatobranchus pulcherrimus Miller & Willan, 1986 is considered here as a new synonym of Dermatobranchus rubidus (Gould, 1852). The following 20 species of Dermatobranchus are new and are described in the present paper: Dermatobranchus albineus sp. nov., Dermatobranchus arminus sp. nov., Dermatobranchus caesitius sp. nov., Dermatobranchus caeruleomaculatus sp. nov., Dermatobranchus cymatilis sp. nov., Dermatobranchus dendonephthyphagus sp. nov., Dermatobranchus diagonalis sp. nov., Dermatobranchus earlei sp. nov., Dermatobranchus fasciatus sp. nov., Dermatobranchus funiculus sp. nov., Dermatobranchus kalyptos sp. nov., Dermatobranchus kokonas sp. nov., Dermatobranchus leoni sp. nov., Dermatobranchus microphallus sp. nov., Dermatobranchus oculus sp. nov., Dermatobranchus phyllodes sp. nov., Dermatobranchus piperoides sp. nov., Dermatobranchus rodmani sp. nov., Dermatobranchus semilunus sp. nov., and Dermatobranchus tuberculatus sp. nov. Eighteen of these new taxa are found in the Indo-Pacific tropics and two are found in temperate South Africa, D. albineus and D. arminus. Unique combinations of morphological characters distinguish these as new species of Dermatobranchus. Several species that are externally similar have radically divergent internal morphology, are members of different clades of Dermatobranchus, and represent cryptic species. Especially important is the radular morphology, which shows remarkable diversity of form, probably related directly to the diversification of feeding of members of this clade on various octocorals.